Economic Perspectives on Investments in Teacher Quality - Plecki, Margaret L. (Education Policy Analysis Archives, 2000)
This article reviews and critiques the ways in which researchers have used both productivity theory and human capital theory in efforts to measure the returns on investments in improving teacher quality. While studies utilizing these theories to measure investment returns provide useful insights, a critical need exists for research that advances our knowledge about the conceptual links between investments in teacher quality policies and improved student performance. The article also discusses several strategies for improving investigations regarding the returns on investments in improving teacher quality, including more refined measurement strategies, clearer conceptual frameworks, and a greater emphasis on resource re-allocation.